2022
DOI: 10.1111/ejn.15808
|View full text |Cite
|
Sign up to set email alerts
|

Largely unaffected auditory and visual sensory processing phenotypes in the evoked potentials of Fmr1 KO2 mice

Abstract: Sensory sensitivity symptoms are common in autism spectrum disorders and fragile X syndrome. Mainly in the auditory modality, disturbed processing has been found in both fragile X patients and the corresponding genetic mouse model, the Fmr1 knockout mouse. Here, we tried to replicate the auditory deficits and assess whether also visual processing is affected, using electroencephalography readouts under freely behaving conditions in the second-generation Fmr1 knockout mice. No differences between wild-type and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…2020 ; Kat et al. 2021 ; Kat and Kas 2022 ). Deoxyribonucleic acid for genotyping was extracted from ear clips using a lysis buffer (100 mM Tris pH 8.0, 200 nM NaCl, 5 nM ethylenediaminetetraacetic acid) with proteinase K (0.2 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2020 ; Kat et al. 2021 ; Kat and Kas 2022 ). Deoxyribonucleic acid for genotyping was extracted from ear clips using a lysis buffer (100 mM Tris pH 8.0, 200 nM NaCl, 5 nM ethylenediaminetetraacetic acid) with proteinase K (0.2 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…EEG recordings were performed between 15 and 27 (experiment 1) or 10 and 13 (experiment 2) wk of age. Before the first resting-state recording animals were tested in auditory and visual ERP paradigms which have been published elsewhere ( Kat and Kas 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Further, preclinical models have highlighted speci c cell types [17,18]and brain structures [19] that may underlie these auditory chirp oscillatory abnormalities, and thus may serve as good targets for pharmacological intervention. Additional preclinical work has suggested that these phenotypes are speci c to the auditory modality [20], further narrowing the eld of inquiry to manageable outcomes. Of interest, many of the novel pharmaceuticals that have showed improvements in the chirp oscillatory phenotype in FMR1 KO mice are not targeted directly at the mGluR theory of FXS, but rather at alternative pathways such as endocannabinoid effects [16] and PDE10A inhibition [15].…”
Section: Introductionmentioning
confidence: 99%